(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The roots of the right to freedom of conscience. Politics and religion in the theological controversies of the 16th century in the context of the Protestant Reformation. Freedom of conscience, as the core of religious freedom, was a right claimed first and foremost against religious authorities, even before political authorities. The solution to the theological controversies that characterised the 16th century and the phenomena of religious intolerance contributed to the political instrument of civil tolerance as the government of the coexistence of several religions within the same territory, as the first step in a process of recognition of religious pluralism.